Discussion on The Teaching Method of External Mandarin for Primary School Students in The Suburbs of Surabaya, Indonesia: 针对印度尼西亚泗水郊区小学生的对外中文教学法探讨 - Adhimas, Yogi Bagus; Arista, Cicik; Chaoqun, Li (Mandarinable: Journal of Chinese Studies, 2023)
Teaching Mandarin in an area where the cultural context can be described as isolated is a challenge in itself. Instead of teaching how to speak directly, prioritize the heart-to-heart approach. Whoever knows how to touch them personally, automatically comes into contact with people who have the same culture. The purpose of this study is to explain that Mandarin education in peripheral areas is better prioritized by cultural approaches. with the basis of research to have more impact on love for Mandarin first, in order to have more motivation to learn and high confidence when learning Mandarin. The findings when the treatment of Mandarin teaching was carried out which emphasized the cultural approach and broke the cliché order of mainstream Mandarin teaching, resulted in children in the periphery being more receptive because of the excitement in the class they got. So, the conclusion is that to be a Mandarin teacher in the countryside, teacher must be a person with the same tribal background to understand the customs. Look for ideas and then work to create creative media. Finally, it provides language ability, not language theory.